Awareness of Patient Physical Handling Issues Associated with Routine Nursing Care - Marie Trešlová; Drahomíra Filausová; Lenka Šedová; Hana Hajduchová (MDPI AG, 2020)
Introduction: Physical handling (PH) of patients is an essential component of nursing care. It is an intervention that is troublesome for patients and strenuous for general nurses and other nursing staff. Handling techniques and mechanical aids for PH have improved through the years; however, they are not routinely used in nursing practice. Aim: The aim of this research was to determine (1) the level of awareness of PH issues within the management of South Bohemian hospitals, (2) how management perceives, organizes and implements PH protocols, and (3) how PH protocols are applied in everyday nursing practice. Method and Research Sample: Two qualitative methods were used: a semi-structured interview and observation. The participants were management representatives of South Bohemian hospitals in Czech Republic. Fifty nurses were observed during PH at the same hospitals. Results: The study found that PH was not monitored, nor was it provided systematically. In spite of this, no serious drawbacks were found; nonetheless, many areas were identified where the quality of PH could be improved. For example, awareness of PH issues by management, educational programs teaching new handling techniques, and provision of state-of-the-art PH aids. Several issues related to PH were found to be related to staff shortages, which remains a major problem. Conclusion: This issue needs more attention; it should be addressed by both those doing nursing research as well as those engaged in everyday nursing practice. Both will require the assistance of hospital staff and management.